2023
DOI: 10.3390/economies11010021
|View full text |Cite
|
Sign up to set email alerts
|

Do Publicly Listed Insurance Firms in Saudi Arabia Have Strong Corporate Governance?

Abstract: Saudi Arabia has now opened its markets to foreign investors in line with its strategy to diversify its economy. However, investors need to feel confident that Saudi enterprises are being monitored and regulated appropriately. This study identifies the impact of improvements in Saudi corporate governance practices among insurance firms. The effects of corporate governance on the financial performance of 35 insurance firms listed on the Saudi stock market are examined from 2008 to 2014, including Shariah-compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…The second hypothesis supports that there is a connection between corporate governance and sustainable financial performance. This finding is consistent with the findings of recent studies (Al-Faryan & Alokla, 2023;Amrani et al, 2022;Dănescu et al, 2021;Mubeen et al, 2021) who discovered a link between corporate governance and sustainable financial performance. Hence, Audit committees and their independence are integral parts of corporate governance, and they ensure the sustainable performance of firms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The second hypothesis supports that there is a connection between corporate governance and sustainable financial performance. This finding is consistent with the findings of recent studies (Al-Faryan & Alokla, 2023;Amrani et al, 2022;Dănescu et al, 2021;Mubeen et al, 2021) who discovered a link between corporate governance and sustainable financial performance. Hence, Audit committees and their independence are integral parts of corporate governance, and they ensure the sustainable performance of firms.…”
Section: Discussionsupporting
confidence: 93%
“…The literature shows that corporate governance practices positively and negatively impact organizational performance, but some studies have mixed (Abdullah & Tursoy, 2023;Al-Faryan & Alokla, 2023;Waris et al, 2023). Several studies have found a significant positive relationship between corporate governance practices and organizational performance indicators, such as return on assets, return on equity, and net income (Aggarwal & Management, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, following earlier studies like Barth et al (2012), Andersen et al (2022), Umar (2022) and Umar et al (2022), the variable was winsorized at 5% to limit the influence of its extreme value. Besides, the VIF statistics are much less than 10, indicating the nonexistence of multicollinearity in our model (Al-Faryan and Alokla, 2023; Gujarati and Porter, 2009). In addition, the tolerance values range between 0.512 and 0.867, which are within the ranges of 1 and 0 established in the literature as the acceptable range (Saidu, 2019).…”
Section: Resultsmentioning
confidence: 78%
“…The country released the strategic Saudi Vision 2030 in 2016 to diversify its economy from relying on oil (Al-Faryan and Shil, 2022; Bamahros et al , 2022). It has also recently opened its markets to international investors to diversify its economy and wean itself off reliance on oil (Al-Faryan and Alokla, 2023). Hence, ESG disclosure by firms in Saudi Arabia is believed to be a vital instrument that can lead to achieving sustainability (Adileh, 2022).…”
Section: Introductionmentioning
confidence: 99%